Dietary supplementation with probiotics improves hematopoiesis in malnourished mice. - Susana Salva (Public Library of Science (PLoS), 2012)
Background Lactobacillus rhamnosus CRL1505 (Lr) administered during the repletion of immunocompromised-malnourished mice improves the resistance against intestinal and respiratory infections. This effect is associated with an increase in the number and functionality of immune cells, indicating that Lr could have some influence on myeloid and lymphoid cell production and maturation. Objective This study analyzed the extent of the damage caused by malnutrition on myeloid and lymphoid cell development in the spleen and bone marrow (BM). We also evaluated the impact of immunobiotics on the recovery of hematopoiesis affected in malnourished mice. Methods Protein malnourished mice were fed on a balanced conventional diet for 7 or 14 consecutive d with or without supplemental Lr or fermented goat's milk (FGM). Malnourished mice and well-nourished mice were used as controls. Histological and flow cytometry studies were carried out in BM and spleen to study myeloid and lymphoid cells. Results Malnutrition induced quantitative alterations in spleen B and T cells; however, no alteration was observed in the ability of splenic B cells to produce immunoglobulins after challenge with LPS or CpG. The analysis of BM B cell subsets based on B220, CD24, IgM and IgD expression showed that malnutrition affected B cell development. In addition, BM myeloid cells decreased in malnourished mice. On the contrary, protein deprivation increased BM T cell number. These alterations were reverted with Lr or FGM repletion treatments since normal numbers of BM myeloid, T and B cells were observed in these groups. Conclusions Protein malnutrition significantly alters B cell development in BM. The treatment of malnourished mice with L. rhamnosus CRL1505 was able to induce a recovery of B cells that would explain its ability to increase immunity against infections. This work highlights the possibility of using immunobiotics to accelerate the recovery of lymphopoyesis in immunocompromised-malnourished hosts.